Pondering Parotid Masses - Mark A Miller (Canadian Journal of Infectious Diseases)
A49-year-old, human immunodeficiency virus (HIV)- infected, Haitian-born woman presented with a left facial mass that she had noticed for the previous eight weeks. She was known to have been HIV-seropositive for the previous 11 years and had been on multiple antiretroviral therapies. Her past medical history was also significant for hypertension, disseminated varicella zoster virus and recurrent oral and buttock Herpes simplex episodes. She was taking the following medications at the time of her presentation with the facial mass: stavudine, lamivudine, didanosine, nelfinavir mesylate, famciclovir, hydrochlorothiazide and cotrimoxazole. She had no complaints of fever, chills, sweats, weight loss or anorexia. She denied any pain, redness or warmth at the site of the facial swelling. Her most recent CD4 lymphocyte count was 336 cells/µL, with an HIV viral load of log102.6 copies/mL. Physical examination revealed a 4 cm fluid-filled mass in the left parotid gland. There was no detectable induration, redness, warmth or tenderness, and no associated adenopathy. The rest of the examination was unremarkable. An aspirate of the mass was performed under sterile conditions and yielded 30 mL of turbid, yellow liquid. A Gram stain revealed no neutrophils, scant mononuclear cells and no visible organisms. An acid-fast stain was negative as well. Routine, mycobacterial and fungal cultures showed no growth. Cytological analysis showed scant reactive lymphocytes and no malignant cells. The patient was not given therapy and was observed for another two months. The fluid reaccumulated in the left parotid gland, and the patient?s only complaint concerned the unsightly appearance of the mass. The lesion was again aspirated for 30 mL of fluid and this time, the fluid had a turbid, brown appearance. All laboratory results were identical to the results from the first aspirate. What is your diagnosis, and how would you treat this patient?